'As an undergrad, I don't have the right to an opinion': Reconstructing Students as Creative Meaning-makers in the Applied English Language Classroom. (August 2017) - Oostendorp, Marcelyn
The transformation of higher education has been a pressing concern for policy makers and practitioners. This article provides examples of the transformative potential of assessments designed within the framework of a multi-literacies and heteroglossic pedagogy in an Applied English Language course at a South African university. These assessments, which used multiple semiotic resources and created spaces for contesting voices, allowed students to bring their own expertise into the learning experience. This, it is argued, ultimately led to enhanced student voice and agency, two crucial components in transformative practices.